Answer:
a₂ = G(m₁ + m₂)/(R - √[G(m₁ + m₂)/a₁])²
Explanation:
Since the gravitation force of attraction of the center of mass on m₁ equals the centripetal force, then
G(m₁ + m₂)m₁/R₁ = m₁a₁ where (m₁ + m₂) = total mass of the system and R₁ = distance of m₁ from the center of mass
So, G(m₁ + m₂)m₁/R₁² = m₁a₁
G(m₁ + m₂)m₁/m₁a₁ = R₁²
R₁² = G(m₁ + m₂)/a₁
R₁ = √[G(m₁ + m₂)/a₁]
The distance of m₂ from the center of mass is thus R₂ = R - R₁ = R - √[G(m₁ + m₂)/a₁] where R is the distance between the two stars.
Also, the gravitation force of attraction of the center of mass on m₂ equals the centripetal force, then
G(m₁ + m₂)m₂/R₂ = m₂a₂ where (m₁ + m₂) = total mass of the system and R₂ = distance of m₂ from the center of mass
So, G(m₁ + m₂)m₂/R₂² = m₂a₂
G(m₁ + m₂)m₂/m₂R₂² = a₂
a₂ = G(m₁ + m₂)/R₂²
Substituting R₂ into the equation, we have
a₂ = G(m₁ + m₂)/(R - √[G(m₁ + m₂)/a₁])²